Prediction of VEGF-C as a Key Target of Pure Total Flavonoids From Citrus Against NAFLD in Mice via Network Pharmacology - Hong, Wei; Li, Songsong; Wu, Liyan; He, Beihui; Jiang, Jianping; Chen, Zhiyun (Frontiers in Pharmacology, 2019)
Pure total flavonoids from Citrus (PTFC) effectively reduce the symptoms of non-alcoholic fatty liver disease (NAFLD). Our previous microarray analysis uncovered the alterations of important signaling pathways in the treatment of NAFLD with PTFC. However, the underlying core genes that might be targeted by PTFC, which play important roles in the progression of NALFD are yet to be identified. In this study, we predicted the vascular endothelial growth factor-C (VEGF-C) as potential key molecular target of PTFC against NAFLD via network pharmacology analysis. The network pharmacology approach presented here provided important clues for understanding the mechanisms of PTFC treatment in the development of NAFLD.